The Value Relevance of Quantity and Quality of Sustainability Reporting: Evidence from Indonesia - Merelyn Merelyn; Rizky Eriandani (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the value relevance of the quantity and quality of sustainability report disclosure by examining its effect on firm value. The population of this research are companies from all sectors that are listed on the Indonesian Stock Exchange and published sustainability reports in 2015-2020. The final sample that meets the research criteria is 267 companies. This study uses a multiple linear regression test model with 3 dependent variables as a proxy for firm value, namely log Tobin's Q (TQ), Return on Assets (ROA), and Market Capitalization (MC). Two independent variables in the model, namely the quantity and quality of sustainability report disclosures are calculated by analyzing the content of the sustainability report according to the 2018 GRI standards. This study provides results where both the quantity and quality of the sustainability report disclosures have no effect on the value of the company, which means they are not value relevant.